MAPPING OF EXISTING MARICULTURE ACTIVITIES IN SOUTH-EAST SULAWESI “POTENTIAL, CURRENT AND FUTURE STATUS” - Hatim Albasri; Wa Iba; La Ode Muhammad Aslan; Geoff Gooley; Sena De Silva (Indonesian Aquaculture Journal, 2010)
The present study identifies existing mariculture activities and its constraints in SE Sulawesi, along with its geo-physical attributes in the Province.This allows for a better understanding the potential, current and future status of mariculture development in the area and making sure its sustainability. The study was conducted to map the existing mariculture activities in SE Sulawesi. Data collection was performed in June 2009. Spatial and attribute data of the existing mariculture were acquired by interviewing fish farmer using open-ended questionnaire and analyzed using ArcGIS 9.x. Key water quality parameters consisted of temperature, dissolved oxygen, pH, salinity, depth, clarity, and turbidity and analyzed using STORET Indeks. Three big clusters of existing mariculture activities are located in Kendari, Muna and Buton areas, collectively serving as both a source of mariculture products and a market destination or transit location. All surveyed locations of existing mariculture activities in SE Sulawesi show relatively optimal water quality conditions. Site capacity and suitability analysis of existing or potential areas of mariculture activities and development have largely not been considered by stakeholders involved in managing coastal areas, resulting in crowded and unmanaged development with multiple overlapping economic activities in some areas. Piloting of integrated ‘value-adding’ mariculture industries (e.g. raw material, processed products and ‘ready to eat’ industries) might help ease some if not all of the existing economic problems of the mariculture sector.